Comparison of manual rasping and robotic milling for short metaphyseal-fitting stem implantation in total hip arthroplasty: a cadaveric study. (January 2013) - Lim, Seung-Jae; Kim, Sang-Min; Lim, Byung-Ho; Moon, Young-Wan; Park, Youn-Soo
<x xml:space="preserve">Abstract</x> Objective: The ROBODOC system offers the theoretical advantage of providing better fit and mechanical stability of the stem in total hip arthroplasty. However, there has been no previous study on short metaphyseal-fitting stem implantation using the ROBODOC system. The aim of the present study was to compare the implant position and primary stability of short metaphyseal-fitting stems implanted by robotic milling and manual rasping in a human cadaveric femoral model. Methods: Eight matched pairs of human cadaveric femora were randomly assigned to a robotic milling group or manual rasping group. Operative time and intraoperative femoral fractures were monitored, and radiographic evaluation of stem alignment was performed by comparison of preoperative planning and postoperative CT data. Stability testing was performed on six matched pairs of femora, excluding two specimens in which intraoperative fractures occurred. Results: The robotic milling procedures took an average of 27 minutes longer than the manual rasping procedures (p < 0.001). The robotic milling group exhibited significantly better anteroposterior alignment and vertical seating, and also showed a significantly reduced variability in both alignment and vertical seating. No intraoperative femoral fracture was detected in the robotic milling group, whereas two femoral fractures and one femoral stem tip perforation were detected in the manual rasping group. Stability testing showed no significant difference in translational and rotational migrations between the two groups, although the robotic milling group showed a trend towards reduced variability of stability. Conclusions: Our cadaveric study suggests that the use of the ROBODOC system for short metaphyseal-fitting stem implantation may have advantages in improving implant fit and reducing the risk of intraoperative femoral fractures without compromising primary stability.